2021
DOI: 10.1038/s41598-021-89657-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference genes for use in untreated bovine fibroblasts

Abstract: Proper normalization of RT-qPCR data is pivotal to the interpretation of results and accuracy of scientific conclusions. Though different approaches may be taken, normalization against multiple reference genes is now standard practice. Genes traditionally used and deemed constitutively expressed have demonstrated variability in expression under different experimental conditions, necessitating the proper validation of reference genes prior to utilization. Considering the wide use of fibroblasts in research and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Therefore, the analysis was also conducted after combining the findings from all the conditions confirming that geNorm, NormFinder, and RefFinder concur regarding the most stable genes ( ACT / G6PD ), whereas BestKeeper once more provided a completely different outcome (Table 2 ). Studies on different organisms have revealed that geNorm, NormFinder, and RefFinder provide similar results, whereas BestKeeper produces a different ranking of gene stability 34 , 40 , 41 . This difference can be partially explained since BestKeeper uses raw Ct values as input 21 , whereas relative quantity (RQ) values are used by geNorm 19 and NormFinder 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the analysis was also conducted after combining the findings from all the conditions confirming that geNorm, NormFinder, and RefFinder concur regarding the most stable genes ( ACT / G6PD ), whereas BestKeeper once more provided a completely different outcome (Table 2 ). Studies on different organisms have revealed that geNorm, NormFinder, and RefFinder provide similar results, whereas BestKeeper produces a different ranking of gene stability 34 , 40 , 41 . This difference can be partially explained since BestKeeper uses raw Ct values as input 21 , whereas relative quantity (RQ) values are used by geNorm 19 and NormFinder 20 .…”
Section: Discussionmentioning
confidence: 99%